2020
DOI: 10.21203/rs.3.rs-60202/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinction Between Vaginal and Cervical Microbiota in High-risk Human Papilloma Virus Infected Women in China

Abstract: Background: High-risk human papilloma virus (hrHPV) is regarded as the main causal factor of cervical precancer and cancer when persistent infection is left untreated. Previous studies have declared that HPV is associated with microecological environment of lower genital tract but haven’t discriminate vaginal microbiota from that of cervix. Objective: To analyze the distinction between vaginal and cervical microbiota in high-risk HPV(+) Chinese women. Methods: One hundred participants were recruited including … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
1
0
1
Order By: Relevance
“…We found that compared with healthy females, the species abundance and diversity of vaginal microbes in HPV-infected patients without LSIL were signifcantly increased, which suggests that there are alterations in vaginal microbes in the early stage of HPV infection. Tis is consistent with the fndings of majority studies [17][18][19] but not consistent with that by Wu et al [20]. Tis may be caused by the regional diferences of the participants.…”
Section: Discussionsupporting
confidence: 47%
“…We found that compared with healthy females, the species abundance and diversity of vaginal microbes in HPV-infected patients without LSIL were signifcantly increased, which suggests that there are alterations in vaginal microbes in the early stage of HPV infection. Tis is consistent with the fndings of majority studies [17][18][19] but not consistent with that by Wu et al [20]. Tis may be caused by the regional diferences of the participants.…”
Section: Discussionsupporting
confidence: 47%
“…Other studies have documented non-difference or a significant reduction in microbial abundance and significant deterioration of Prevotella in the case of a chronic HPV infection. Zhang et al [82] found no difference in Prevotella abundance in different HPV-positive populations. Guerrero-Preston et al [83] did a cross-sectional comparison of the microbial communities present in salivary DNA from HPV-positive and HPV-negative patients with cancer of the oropharynx, cancer of the oral cavity, and normal oral cavity epithelium.…”
Section: Human Papillomavirus (Hpv)mentioning
confidence: 96%
“…В останні роки отримано нові дані про зміну етіологічної структури у разі проліферативних процесів цервікального каналу та ендо-і міометрія, зокрема такі, як домінування вірусної та умовно-патогенної флори та переважання мікробних асоціацій із більш вираженими патогенними властивостями у мікрофлорі піхви [8, [10][11][12]14,16].…”
Section: акушерство та гінекологіяunclassified